Empowering house purchasers: a focus on Malaysian Tribunals for homebuyers' claim - Sufian, Azlinor (2011)
Being one of the developing countries, to have a proper and structured mechanism in relation to land, housing and property development is something that can be proud of. This is considered as part of the mechanism that will support the growth of these areas. This is also related to the confidence that public will have towards the property developers. In Malaysia, the Tribunal for Homebuyers’ Claim has been established in the year of 2002 to enable house purchasers to file a claim against property developers for any problem related to housing development. It is the objective of this paper to discuss the provisions, rules and procedures relating to the Tribunal for Homebuyers’ Claim that is specifically regulated by the Housing Development (Control and Licensing) Act, 1966 and the Tribunal for Homebuyers’ Claim Regulations, 2002. It is hoped that the Malaysian government will improve the laws and regulations governing this tribunal and thus need to study the experiences and practices in other jurisdictions.